Functional polymorphism in miR-208 is associated with increased risk for ischemic stroke - Chao Liu; Yan-Ping Luo; Jie Chen; Yin-Hua Weng; Yan Lan; Hong-Bo Liu (BMC, 2023)
Abstract Background The miR-208 gene is one of the microRNAs now under active studies, and has been found to play significant roles in an array of cardiovascular diseases. Nevertheless, until now, no studies have examined the relationship between the susceptibility to ischemic stroke (IS) and genetic variations in miR-208. This study explored the association between the miR-208 polymorphisms (rs178642, rs8022522, and rs12894524) and the risk of IS. Methods A total of 205 cases of IS and 211 control subjects were included. The SNPscans genotyping test was employed to determine the genotypes of the three polymorphisms. Results Significant correlation was observed between rs8022522 polymorphism and risk of IS on the basis of analyses of genotypes, models and alleles (GA vs. GG: adjusted OR = 2.159, 95% CI: 1.052-4.430, P = 0. 036; AA vs. GG: adjusted OR = 5.154, 95% CI: 1.123-23.660, P = 0.035; dominant model: adjusted OR = 1.746, 95% CI, 1.075-2.838, P = 0.025; G vs. A: adjusted OR = 2.451, 95% CI: 1.374-4.370, P = 0.002). Conclusions The rs8022522 polymorphism of the miR-208 gene is significantly associated with an elevated risk of ischemic stroke in Chinese.